2017
DOI: 10.1186/s12939-017-0559-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence maternal background has on children’s mental health

Abstract: BackgroundIn this paper, we aim to discern how a mother’s health and her socioeconomic determinants may influence her children’s mental health. In addition to this, we also evaluate the influence of other household characteristics and whether or not the economic downturn has heightened the effect a parent’s social gradient has on their children’s mental health.MethodsWe use samples comprised of 4-14-year-old minors from the 2006 Spanish National Health Survey (SNHS), undertaken prior to the crisis, and the 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 46 publications
4
47
1
5
Order By: Relevance
“…This is similar to studies done by Arroyo-Borrell et al, and Etherington et al, which shows mother's literacy status is one of the independent predictors of possible depression during adolescence. 21,22 Physical activity produces natural changes in the body which helps alleviate depressive symptoms. 9 Physical activity is one modifiable factor which can be used to reduce the risk of developing depression and as an effective adjuvant in treatment plan for depression.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to studies done by Arroyo-Borrell et al, and Etherington et al, which shows mother's literacy status is one of the independent predictors of possible depression during adolescence. 21,22 Physical activity produces natural changes in the body which helps alleviate depressive symptoms. 9 Physical activity is one modifiable factor which can be used to reduce the risk of developing depression and as an effective adjuvant in treatment plan for depression.…”
Section: Discussionmentioning
confidence: 99%
“…Las consecuencias a largo plazo de las privaciones de los niños de hoy serán previsiblemente importantes en el futuro (Flores et al, 2014), de ahí que se abogue por la intervención pública temprana desde sectores como la educación para garantizar una nutrición adecuada. Arroyo-Borrell et al (2017), utilizan la ENS para analizar si el estado de salud de las madres y sus determinantes socioeconómicos pueden influir en la salud mental de los hijos. Entre los principales resultados mostrados por las autoras cabe destacar la identificación de que el riesgo del niño a padecer un desorden mental se incrementa con los problemas mentales de la madre.…”
Section: Problemas De Salud En Grupos Seleccionadosunclassified
“…This lack of association was corroborated by another study in Andalusia which, instead, found that the negative impact of the recession on mental health was concentrated amongst those with secondary education, whether employed or unemployed (Córdoba-Doña et al, 2016) The impact of the financial crisis on mental health appears to have differed between age groups. Specifically, the risk of suffering from mental health problems for children with unemployed parents was higher in 2011 compared to 2006 (Arroyo- Borrell et al, 2017). However, the apparent effects of the crisis on the mental health of the young population vary according to the data source (Aguilar-Palacio et al, 2015; Medel-Herrero and Gómez-Beneyto, 2017).…”
Section: Mental Health Outcomesmentioning
confidence: 99%